Community engagement through public programs in art and cultural ınstitutions in Istanbul - Çelen, Miyase (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: With the change of socio-cultural atmosphere, the social function of art and cultural institutions and their relations with society has gained more importance. It is an ongoing debate that the relationship between art and cultural institutions and the public has been transformed or should be transformed. The active engagement of communities in art institutions is not a new discussion however, it becomes a necessity in many ways in the 21st century instead of being just a beneficial tool. This thesis explores the relations between art and cultural institutions and society through public programs based on the discussions about the role of contemporary art institutions in democratic societies. The point where these programs make a difference is that they are no longer seen as just a method for audience development, but instead these programs allow the active participation of communities, interprets social trends, and responsive to current interests, problems, and debates, as institutions abandon their authoritarian and didactic approaches. The thesis examined the community engagement practices of SALT, Arter, and Istanbul Modern, which are among the impactful art and cultural institutions in Istanbul, through the selected public programs as cases and in this way, evaluated the relationship of these institutions with their users. The study questions why community engagement is regarded as important, how public programs create opportunities and how it is implemented in art and cultural institutions in Istanbul through public programs; data obtained from interviews with relevant departments from selected institutions were used in addition to literature research. The concepts of community and community engagement, the development of community engagement discussions and the trends that have influenced today's practice, and the main debates about the active engagement of the society in art and cultural institutions are analyzed. Afterward, it is aimed to examine the ongoing discussions in this field in terms of modern and contemporary art and cultural institutions in Istanbul.

ÖZET: Sanat ve kültür kurumlarının toplumsal rolleri ve toplumla ilişkileri günümüzde daha çok önem kazanmıştır. Değişen sosyo-kültürel atmosferde, kültür ve sanat kurumlarının kamuyla ilişkisinin dönüşüm geçirdiği veya dönüşmesi gerekliliği süregelen bir tartışmadır. Farklı komünitelerin sanat kurumlarında aktif olarak yer alması yeni bir tartışma olmasa da bu durumun 21. yüzyılda sadece yarar amaçlı olmaktan çıkıp, birçok anlamda zorunluluk haline gelmesi istenmektedir. Bu tez, çağdaş sanat kurumlarının demokratik toplumlardaki rolünün ne olduğu tartışmalarından yola çıkarak toplumla ilişkilerini, bu kurumların düzenlediği kamu programları üzerinden incelemektedir. Bu programların fark yarattığı nokta, kurumların bu programları artık sadece kullanıcı geliştirme için bir yöntem olmaktan çıkıp kurumun otoriter ve didaktik rolünden sıyrılarak komünitelerin aktif katılımına; sosyal eğilimlere ve mevcut ilgi, sorun ve tartışmalara yanıt vermeye olanak sağlayan programlar olmasıdır. Tez, İstanbul’daki etkili sanat ve kültür kurumlarından SALT, Arter ve İstanbul Modern’in komünite katılımı uygulamalarını, seçilen kamu programı örnekleri üzerinden incelemiş ve bu yolla bu kurumların kullanıcısıyla olan ilişkisini değerlendirmiştir. Komünite katılımının neden gereklilik olarak kabul edildiği, kamu programlarının kullanıcılarının katılımı için nasıl fırsatlar yarattığı, Türkiye'deki sanat ve kültür kurumlarında katılımın kamu programları yoluyla nasıl uygulandığı soruları ekseninde bu çalışmada; literatür araştırmasının yanında, seçilen kurumlarda ilgili departmanlardaki kişilerle gerçekleştirilen röportajlardan elde edilen veriler kullanılmıştır. Komünite, komünite katılımı kavramları tanımlanmış, komünite katılımı tartışmalarına nasıl gelindiğini anlayabilmek için bugünün pratiğine etki eden akımlar ve toplumun sanat ve kültür kurumlarına aktif katılımıyla ilgili temel tartışmalar incelenmiştir. Bu alanda devam etmekte olan tartışmaların, İstanbul’daki modern ve çağdaş sanat ve kültür kurumları özelinde incelenmesi amaçlanmıştır.
İstanbul'da sanat ve kültür kurumlarında kamu programları yoluyla komünite katılımı
Keywords: Komünite; Komünite Katılımı; Kamu Programları; Sanat ve Kültür Kurumları; Öğrenme; Community; Community Engagement; Public Programs; Art and cultural institutions